2014
DOI: 10.21608/zumj.2014.4360
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Primary Immunodeficiency Disorders Among Children at Zagazig University Hospital

Abstract: Aim of study: To identify and report various type of primary immunodeficiency disorders in children at Zagazig university hospitals, and their characteristic features, clinical manifestations and laboratory profiles. Patients and methods; patients with history,clinical findings and laboratory findings matching with any of eight classes of primary immunodeficiency were included in this study, also we used ten warning signs,immunodediciency disease related score in evaluation of patients. Results: Fifty patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…Males were affected more than females, a trend seen in other parts of the world, including Europe and India10,11. The ages reported in the present study were earlier than the previously estimated12, in Zagazig who reported that the median onset age of symptoms was 7 months (range, 1–84 months) and the median age at diagnosis was 24 months (3–120 months). Zeng et al13 in their study from South China reported a median age at diagnosis of 10 months range (2–159 months).…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Males were affected more than females, a trend seen in other parts of the world, including Europe and India10,11. The ages reported in the present study were earlier than the previously estimated12, in Zagazig who reported that the median onset age of symptoms was 7 months (range, 1–84 months) and the median age at diagnosis was 24 months (3–120 months). Zeng et al13 in their study from South China reported a median age at diagnosis of 10 months range (2–159 months).…”
Section: Discussioncontrasting
confidence: 42%
“…Recurrent deep-skin and organ abscesses and deep-seated infections were significantly more frequent in the category of congenital defects in phagocyte number, function, or both. In Zagazig, Egypt another study done by A Hussien et al12, over a period of two years including 50 patients found pneumoniae, bronchitis and otitis media were the most common presentations in PID patients. Recurrent severe infections as pneumonia, chronic diarrhea, and failure to thrive are commonly thought of as classic symptoms of PID and patients with combined lower respiratory tract infections, fungal infections and lymphopenia were 12.3 times more likely to be diagnosed with a PID disorder.…”
Section: Discussionmentioning
confidence: 97%
“…In a study on healthy Egyptian children, the level of TRECs and KRECs was found to be inversely proportional to age (46). The lowest threshold of TRECs (copies/µl blood) was 25 for the group aged 1 day to 5 months, and 24 for the group aged 5 months to 2.4 years.…”
Section: Status In Egyptmentioning
confidence: 96%
“…Data on the prevalence of PIDs in Egypt is lacking as there is no national registry to date. The ESID database contains data from Egypt and some information can also be gained from the few published studies (33,(45)(46)(47). CID is considered the most common disease (31%), followed by predominantly antibody deficiency (30%), welldefined syndromes with PID (17.5%), and, finally, phagocytic defects (8.1%).…”
Section: Status In Egyptmentioning
confidence: 99%